GHG balance, its seasonality and response to soil type and management of northern agricultural grasslands: Eddy-covariance flux measurements from three adjacent fields in Finland - Shurpali, Narasinha; Peltola, Olli; Li, Yuan; Manninen, Petra; Semberg, Sanni; Launiainen, Samuli; Louhisuo, Arja; Rinne, Janne; Järvinen, Mikko; Virkajärvi, Perttu; Martikainen, Pertti J (My University, 2025)
Understanding how managed grasslands respond to climate and management regimes across global pedoclimatic zones is crucial to combating climate change. In this study, we used the eddy covariance method to continuously measure GHG fluxes from January through December 2022 at three boreal grassland sites in eastern Finland: Anttila on mineral soil, and Särkisuo and Pappilansuo on drained peat soils. Our results highlight significant seasonal variability and a strong dependence on management events (such as summer plowing at Pappilansuo, fertilization, and harvest at all three sites). The net CO2 exchange ranged from a strong net uptake at Anttila (–2500 kg C ha−1 yr−1) and moderate uptake at Särkisuo (–500 kg C ha−1 yr−1) to net release at Pappilansuo (+930 kg C ha−1 yr−1). CH4 fluxes were negligible at Anttila (total of +2 kg CH4 ha−1 yr−1) but reached + 110 kg CH4 ha−1 yr−1 at Särkisuo and + 51 kg CH4 ha−1 yr−1 at Pappilansuo. N2O emissions peaked after fertilization with + 3.8 (Anttila), + 16 (Särkisuo), and + 29 kg N₂O ha−1 yr−1 (Pappilansuo). Anttila remained a net GHG sink at approximately –8.0 t CO2-eq ha−1, whereas Särkisuo and Pappilansuo were net sources of 5.0 and 12.3 t CO2-eq ha−1, respectively. Anttila had the lowest GHG emissions per kilogram of grass biomass produced and had the highest yield, illustrating the potential for more climate-friendly grassland management on suitable soils. However, the organic soils showed higher GHG emissions. These results highlight the influence of soil type and the importance of management timing on the overall GHG balance in boreal grasslands.
Keywords: carbon sequestration; climate change mitigation; eddy covariance; grassland management